Hak Angket Dewan Perwakilan Rakyat Republik Indonesia Sebagai Fungsi Pengawasan Lembaga Negara - Kristiawanto Kristiawanto (Universitas Jayabaya, 2020)
This study aims to examine that the fundamental problem is the use of the inquiry right of the House of Representatives of the Republic of Indonesia to the Corruption Eradication Commission. The research method used is the normative juridical legal research type, the researcher uses four approaches, namely the statute approach, the case approach, the conceptual approach and the comparative approach. The legal materials used in this study are primary legal materials, secondary legal materials and tertiary legal materials. Procedures for collecting legal materials based on problem topics that have been formulated in the formulation of the problem and reviewed and analyzed. Whereas the processing and analysis of legal materials by describing and linking them in such a way that they are presented in systematized writing. The results found that the Authority through the functions are clearly given by the right of inquiry is the right of Parliament to conduct an investigation into the implementation of a law and/or policy of the Government with regard to the important things, strategically, and have broad impact on society, nation, and state allegedly contrary to statutory regulations. The mechanism for using the DPR’s inquiry rights against the KPK can be concluded that the KPK is the subject of the DPR’s inquiry right in its supervisory function.